2019
DOI: 10.1109/tnsre.2019.2929544
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired Balance Control Assistance Can Reduce Metabolic Energy Consumption in Human Walking

Abstract: The amount of research on developing exoskeletons for human gait assistance has been growing in the recent years. However, the control design of exoskeletons for assisting human walking remains unclear. This paper presents a novel bio-inspired reflex-based control for assisting human walking. In this approach, the leg force is used as a feedback signal to adjust hip compliance. The effects of modulating hip compliance on walking gait is investigated through joint kinematics, leg muscle activations and overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
0
21
0
1
Order By: Relevance
“…This method was implemented on the LOPES II exoskeleton to assist human walking (Zhao et al, 2017). The results revealed that the force feedback system could reduce the human metabolic cost of walking (Zhao et al, 2019), as well as the consumed power in the assistive device. Inspired by these findings, the main contribution of the FMCA approach is to introduce a new technique to determine the desired ankle impedance using online GRF feedback.…”
Section: E6-2mentioning
confidence: 99%
“…This method was implemented on the LOPES II exoskeleton to assist human walking (Zhao et al, 2017). The results revealed that the force feedback system could reduce the human metabolic cost of walking (Zhao et al, 2019), as well as the consumed power in the assistive device. Inspired by these findings, the main contribution of the FMCA approach is to introduce a new technique to determine the desired ankle impedance using online GRF feedback.…”
Section: E6-2mentioning
confidence: 99%
“…Recent studies with exoskeletons that developed "assistwhen-needed" approaches to support balance were primarily focused on hip control [15][16][17]. The proposed controllers, provide hip torque to adjust the stepping location, either by supporting hip abduction-adduction (step-width adaptation) or hip flexion-extension (step-length adaptation).…”
Section: Introductionmentioning
confidence: 99%
“…The proposed controllers, provide hip torque to adjust the stepping location, either by supporting hip abduction-adduction (step-width adaptation) or hip flexion-extension (step-length adaptation). The assistance is triggered and modulated when perturbations are detected by using different feedback signals, such as the hip angle [15], the extrapolated center of mass (XcoM) [16], or the estimated leg force [17]. These approaches are not intended to replace human control, but rather to augment the user's balance by providing the re-quired assistance in synergy with the human wearer just after the onset of an imminent fall.…”
Section: Introductionmentioning
confidence: 99%
“…50 Template-based control concept of GRF feedback: In [36], the force 51 modulated hip compliance (FMCH model) was introduced as a template for posture 52 control in which the GRF (ground reaction force) was used to tune the hip joint 53 compliance. This method was later implemented in the LOPES II exoskeleton to assist 54 human walking [37,38]. The results revealed the advantages of using the force feedback 55 in reducing the human metabolic cost of walking.…”
mentioning
confidence: 99%
“…will be reflected in the GRF patterns, our ABC control approach has sufficient sensory 602 information to adapt. 2) Actuation level: The force (GRF) modulated compliance 603 model which is based on the VPP concept was already applied for control of LOPES-II 604 exoskeleton in our previous studies [37,38]. In addition to lack of swing phase control in 605 the LOPES experiments, for implementing the FMC (GRF-based control) in such a 606 rigid exoskeleton, the two single joint actuators were used to emulate the biarticular 607 actuation.…”
mentioning
confidence: 99%